ANALISIS FAKTOR-FAKTOR KETIDAKSESUAIAN PELAKSANAAN SOP RETENSI DOKUMEN REKAM MEDIS DI RSU PKU MUHAMMADIYAH ROGOJAMPI TAHUN 2021 - Yanti, Riska Devi (Jurnal Ilmiah Kesehatan Media Husada, 2023)
RSU PKU Muhammadiyah Rogojampi has retained medical record documents in 2021, but in its implementation there are still obstacles and it is not in accordance with the SOP. The purpose of this study was to determine the factors causing the non-compliance with the implementation of the SOP for the retention of medical record documents at PKU Muhammadiyah Rogojampi General Hospital. This type of research is descriptive with a qualitative approach. Data collection techniques in this study was by interviewing with officers who carried out retention of 7 people and observation techniques. Based on the results of the study, it was found that several causes of discrepancies in the implementation of the SOP for the retention of medical record documents at RSU PKU Muhammadiyah Rogojampi, in terms of the man factors, the number of staff is still lacking, most of the officers with educational backgrounds are not medical recorders, the tenure of the filing officer is less, and the staff is not have never attended training on retention. In terms of machine factors, the scanning process for medical record documents that have been assessed is not carried out, in terms of method factors, there is no policy and retention is not carried out in accordance with SOP, and in terms of material factors there is no special space and shelves for inactive medical record documents. Keywords: factors;SOP;medical record retention.